Pediatric cardiologySpontaneous closure of a large atrial septal defect in an infant - Fiszer, Roland; Szkutnik, Małgorzata; Chodór, Beata; Białkowski, Jacek (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
We describe a patient who, at the age of 6 months (body weight 6.1 kg), was diagnosed with a large atrial septal defect (with diameter 10–11 mm) that had spontaneously closed in a 1-year period. The timing of transcatheter intervention in children should be considered individually, paying close attention to subsequent echocardiographic data.